The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuroimage.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating relations between fMRI, ECoG, and EEG through a common natural stimulus

Abstract: Human brain mapping relies heavily on fMRI, ECoG and EEG, which capture different physiological signals. Relationships between these signals have been established in the context of specific tasks or during resting state, often using spatially confined concurrent recordings in animals. But it is not certain whether these correlations generalize to other contexts relevant for human cognitive neuroscience. Here, we address the case of complex naturalistic stimuli and ask two basic questions. First, how reliable a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 68 publications
(104 reference statements)
4
48
0
Order By: Relevance
“…The first result of this study is that for each of the three bands considered there is a large degree of ISC in response to a naturalistic stimulus, irrespective of its emotional content. This finding mirrors evidences from fMRI studies that showed that ISC involves, although with a varying strength, all of the cortical surface (Chang et al, 2015;Chen et al, 2016;Hasson et al, 2004), and replicates the evidence that watching a movie prompts a strong ISC also in the electrical activity collected on the scalp (Haufe et al, 2018). The analysis showed different ISC topographies for the three bands considered, with a gradient of reducing topographical spread of the ISC, transitioning from slow to fast activity.…”
Section: Discussionsupporting
confidence: 85%
“…The first result of this study is that for each of the three bands considered there is a large degree of ISC in response to a naturalistic stimulus, irrespective of its emotional content. This finding mirrors evidences from fMRI studies that showed that ISC involves, although with a varying strength, all of the cortical surface (Chang et al, 2015;Chen et al, 2016;Hasson et al, 2004), and replicates the evidence that watching a movie prompts a strong ISC also in the electrical activity collected on the scalp (Haufe et al, 2018). The analysis showed different ISC topographies for the three bands considered, with a gradient of reducing topographical spread of the ISC, transitioning from slow to fast activity.…”
Section: Discussionsupporting
confidence: 85%
“…Combining analysis of methods spanning the range of space and time will show where the granularity of our linking hypotheses fail (cf. Haufe et al, 2018).…”
Section: Methodsological Issues Are Theoretical Issuesmentioning
confidence: 99%
“…In the simplest case, computing temporal ISCs across a movie or spoken narrative provides insights into the reliability of stimulus locked neural responses across subjects . However, by capitalizing on a shared naturalistic stimulus, ISC analyses can also be used to measure commonalities in stimulus-evoked processing across imaging modalities, such as fMRI, ECoG, EEG, and fNIRS (Mukamel et al, 2008;Liu et al, 2017;Haufe et al, 2018). In this context, ISCs reflect neural signals captured by both measurement modalities.…”
Section: Applications Of Isc Analysismentioning
confidence: 99%
“…Band-pass filtering brain activity measurements to that frequency band can help zoom in on a function of interest. Multi-modal approaches combining fMRI with high-temporal-resolution technologies such as EEG and ECoG can provide insights as to what frequency bands contribute most to ISCs (Mukamel et al, 2008;Liu et al, 2017;Haufe et al, 2018).…”
Section: Box 1 Spatiotemporal Considerationsmentioning
confidence: 99%